Demonstration Of Building Materials Utilization In Traditional Mosque In Mosul, Iraq From 1100s To 1800s Ad - Yahya, Hafedh Abed; Abdul Samadb, Muna Hanim (Universiti Sains Malaysia, 2016)

(untitled)
Architectural design defined as “the method of organizing materials and forms in a specific way to satisfy a definite purpose”. The material is one of the tools used in the process of architectural design as specific part of design solution. In order to identify the architectural characteristics and variations in traditional mosques designs, field survey of the building materials of historical mosque was conducted. Local materials used in construction of mosques in six regions identified. According to role of building materials availability in different regions all over the world where Islam was spread, four types of mosques were concluded. Twelve mosques were selected as sample of the study. Each mosque was analysed in terms of its components and materials used for architectural elements. The findings of the study demonstrate the aspects of using traditional building materials in the architectural elements of the historic mosques.